O princípio da confiança legítima no regime jurídico dos atos autorizativos em matéria ambiental - Senn, Adriana Vanderlei Pommer (2013)
This research examines the principle of legitimate confidence in juridical system of the environmental licensing, and suggests to its application as its limit the retroactivity of the authorizations environmental acts. Suggests that, although their operative approach is bound under the guarantee of state interventive actions against individuals, its application can also be justified by its consideration on the condition of principle, from the standpoint of protection of diffuse interests as related manifestations of right to an ecologically balanced environment. The use of ecological balance indicates that it is not always the result of completion of relations involving the principle may be justified across the board, the protection of legal positions of individuals, or even the protection of the environment as absolute imperative. In this scenario, the conditions of application of the principle suggest a dynamic relationship that is conditioned and connected with a set of new principles of growing concern for environmental and administrative law, such as the precautionary principle, the prohibition of retrogression, and the admission of a defining a minimum existential environment. The administrative acts are examined with emphasis on the environmental license, whose legal revisable and unstable reinforce the reality of the first flexible approach traditionally associated with the definition of the protection of trust. Thus, the paper argues that the principle requires the organization of a legal regime, and different application conditions, whose development is proposed as a solution not more protective of individual interests, but as a relevant alternative to the enhancement and improvement of protection environment.